Diagnostic accuracy of faecal calprotectin in patients with active perianal fistulas. Issue 4 (May 2019) - Stevens, Toer W; D'Haens, Geert R; Duijvestein, Marjolijn; Bemelman, Willem A; Buskens, Christianne J; Gecse, Krisztina B
Background: Faecal calprotectin (FC) is a marker of mucosal inflammation. Objective: The aim of this study was to determine the diagnostic accuracy of FC to (a) differentiate between perianal fistulizing Crohn's disease (pCD) and cryptoglandular perianal fistulas; and (b) detect mucosal inflammation in pCD. Methods: Patients with active perianal fistulas who had FC measured and a complete ileocolonoscopy within 10 weeks were retrospectively included. Results: Fifty-six patients were included (pCD, n  = 37) of whom 19 pCD patients exhibited ulcers. FC was significantly higher in pCD compared to cryptoglandular fistulas (µg/g) (708.0 (207.0–1705.0) vs 32.0 (23.0–77.0), p  < 0.001). Area-under-the-curve (AUC) value for FC receiver operating characteristic (ROC) statistics was 0.900. Optimal FC cut-off was ≥ 150 µg/g. To differentiate pCD from cryptoglandular fistulas in the absence of luminal inflammation, optimal cut-off remained ≥ 150 µg/g (AUC = 0.857, sensitivity = 0.81, specificity = 0.89, positive predictive value (PPV) = 93.8% and negative predictive value (NPV) = 70.8%). In pCD, FC was significantly increased in the presence of ulcers (1672.0 vs 238.0, p  = 0.004). Optimal cut-off was ≥ 250 µg/g (AUC = 0.776; sensitivity = 0.89, specificity = 0.56, PPV - 68.0% and NPV = 83.0%). Conclusion: FC discriminates pCD from cryptoglandular fistulas, even in the absence of intestinal ulcers. In active pCD, an elevated FC does not accurately predict the presence of ulcers and should be interpreted with caution.